RADIATION USE EFFICIENCY AND SOIL WATER CONTENT ON MAIZE-MUNGBEAN INTERCROPPING - Laode Sabaruddin; L.M. Harjoni Kilowasid; Hasbullah Syaf; La Ode Afa; Lies Indriani (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
Mungbean is traditionally intercropped with maize by small-scale farmers which do widely in the tropics, including Southeast Sulawesi.  This study aims  to  assess the radiation use efficiency (RUE) and soil water content (SWC) in maize intercropped with mungbean. The research was arranged on Split-Plot Design of  two factors, i.e. dose of “komba-komba” compost as the main plot consists on 5 t ha-1 and 10 t ha-1 and planting time of mungbean as a subplot, consists on planting mungbean with maize at the same time, delayed planting of mungbean 7 and 14 days after planting (DAP) of maize.  The results shown  that the highest RUE of maize 2.69 g MJ-1 and 3.15 g MJ-1 obtained on komba-komba compost dose 10  t ha-1 and planting mungbean 7 DAP of maize, while highest RUE of mungbean  0.31  g MJ-1  and  0.60  g MJ-1  obtained  on  komba-komba compost dose 10 t ha-1 and planting mungbean and maize at the same time, respectively.  The  soil  temperature  has  negatively correlated with  (SWC)  that  at  the  komba-komba compost with rxy = - 0.7422 and at the time planting of mungbean in intercropping with maize with rxy = - 0.7922.